Biomimetic anisotropic hydrogels: Advanced fabrication strategies, extraordinary functionalities, and broad applications. (February 2022) - Mredha, Md. Tariful Islam; Jeon, Insu
Highlights: Bioinspiration and biomimetics are critical for designing anisotropic hydrogels. Advanced fabrication methods and their critical design strategies are scrutinized. Superior functions than those of their isotropic counterparts exhibited. A broad range of biomedical and engineering applications are presented. Shortcomings, challenges, and comprehensive future guidelines are suggested. Abstract: A variety of soft, hydrogel-like materials with sophisticated micro- and nanoengineered ordered structures that offer excellent functionalities exist in nature. Conventional synthetic hydrogels have an isotropic structure; therefore, they lack many of the functions of the aforementioned natural materials. Anisotropic hydrogels, which possess characteristics similar to that of natural analogs, have been receiving considerable attention in recent years because they display superior and new functionalities that their isotropic counterparts fail to exhibit. Although complex ordered structures are readily generated in nature, engineering such structures in bulk hydrogels has proven to be challenging. These materials contain considerable amounts of water, which makes their polymer interactions and microscale structures difficult to control. In this review, recently developed biomimetic anisotropic hydrogels are discussed systematically, along with state-of-the-art fabrication techniques, critical design principles, and superior functionalities. The extraordinary functionalities of anisotropic hydrogels make them promising candidates for applications in various fields. We reviewed their potential use in several areas, such as those involving tissue engineering, cell control, artificial implants, drug delivery, microfluidics, smart actuators and sensors, soft robotics, flexible electronics, and gel electrolytes for supercapacitors. Finally, the existing challenges and future implications in terms of fabrication, functionalities, and applications of these materials are outlined.